-20-6k=-k

Simple and best practice solution for -20-6k=-k equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -20-6k=-k equation:


Simplifying
-20 + -6k = -1k

Solving
-20 + -6k = -1k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add 'k' to each side of the equation.
-20 + -6k + k = -1k + k

Combine like terms: -6k + k = -5k
-20 + -5k = -1k + k

Combine like terms: -1k + k = 0
-20 + -5k = 0

Add '20' to each side of the equation.
-20 + 20 + -5k = 0 + 20

Combine like terms: -20 + 20 = 0
0 + -5k = 0 + 20
-5k = 0 + 20

Combine like terms: 0 + 20 = 20
-5k = 20

Divide each side by '-5'.
k = -4

Simplifying
k = -4

See similar equations:

| 3x-x+2=22 | | 2x^(1/2) | | 27=y/3-13 | | -2*3-3y=-7 | | 4w-22=8w-70 | | 4x+8x^2=9 | | -17g-4=14-8g | | log(45/x)=0.34 | | -96=-6g+2g | | -2*4-3y=-7 | | 2x-24x=-72 | | -8h+10=-9h+18 | | p^2-2p=-1 | | -9f-6f=24 | | -2*2-3y=-7 | | X^5=65 | | 6=v+5v | | 48=5y-12 | | -3-4z=-15 | | 9x-6=12x-3x | | 3(-2x-1)=2x+5 | | 4(1+5g)= | | 4x+12+2x= | | 4(1+5g)=Submit | | (5x-2)+(2x+8)+90=180 | | 11j-6j+4j=18 | | 7(4p+1)= | | 2x^5=130 | | 2(1+3n)= | | 5(2+5h)= | | 4x-5=-x-5 | | 135x=4 |

Equations solver categories